Weartest of details of the roller bearing of the heavy modes of exploitation. 2.Theoretical ground - Гайдамака, А.В. (Problems of Tribology, 2014)
In work, on the basis of theory of similarity and design are developed and experimentally the tested criteria of similarity of model and model tests on tearing down of surfaces of friction of sliding of details of bearing of rolling on the example of interfaces of “ring of separator – basing ring” and butt “end of roller – side of ring” of cylinder ball bearinng of type 2726, that set the wheeled pairs of freight and passenger carriages.